The nature of prostitution Crimes and their risks to Society: A field Study on inmates of the Rehabilitation school for Juveniles Sentenced in Baghdad - Abdulaziz, Ahmad Abdulaziz; Hussein, Hussein Ali Saeed (Al-Adab Journal, 2022)
the crime of prostitution is a crime of another kind that is committed ma hidden manner far from the eyes of the People. It does not show direct effects on Society and threatens people in their lives and money. However, it Causes negative effects on the moral and ideological structure of Society, by encouraging immorality and moral and ethical degradation in social relation between men and women in such a way that its rates are likely to escalate in our dear country, and this type of crime is clearly evident in the crimes of prostitution. This study dealt with a methodological framework in which it defined the problem of the study, the objectives of the study and terminology related to this study. This crime, including the material element, the moral element, and the accustomed pillar to prostitution, also dealt with the difference between prostitution and crime, and the risks, of the crime of prostitution on Society dealt with Solutions and recommendations, and then that conclusion.